THE HYDROLOGICAL AND ENVIRONMENTAL ASPECT OF LOW FLOW ASSESSMENT IN UNGAUGED BASINS – A CASE STUDY IN THE JUŽNA MORAVA RIVER BASIN - Borislava Blagojević; Vladislava Mihailović; Jovan Blagojević; Dragan Radivojević (Facta Universitatis. Series: Architecture and Civil Engineering, 2021)
Eighteen low flow indicators are considered in the research of sixteen hydrological stations in the Južna Morava river basin. The indicators are estimated by statistical analysis and grouped as hydrological and environmental indicators. A cross-correlation between all indicators is assessed. Environmental flows at hydrologic stations are obtained by the GEP method. The environmental low flow indicators are transferred to two small ungauged basins by regression with physiographic characteristics. The adjustment of environmental flows at ungauged basins is performed according to the locations of the donor stations in the hydrogeological regions of the studied area.